A stable and efficient meshfree Galerkin method with consistent integration schemes for strain gradient thin beams and plates - Wang, B.B.; Lu, Chunsheng; Fan, C.Y.; Zhao, M.H. (ELSEVIER SCI LTD, 2020)
© 2020 Elsevier Ltd